Of Risk Taking and the Personal Distribution of Income - Kanbur, S. M. (Journal of Political Economy, 1979)
This paper revisits the analysis of risk taking and income distribution pioneered by Friedman, but in an extended–general equilibrium–framework. The results of this paper cast doubt on the generality of many of Friedman's strong propositions. In particular, we find that the relationship between inequality and liking for risk is not necessarily monotonic. Nor is it the case that greater diversity in tastes for risk necessarily contributes to greater inequality. The paper also analyzes the effect of progressive taxation on national income and inequality in the context of risk taking.